FAKTOR PENENTU KEPUASAN DAN MINAT KUNJUNG ULANG EKOWISATA - Ristya Primadi; Megawati Simanjuntak; Istiqlaliyah Muflikhati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Satisfaction becomes an essential factor in knowing how high the tourist interest to make a revisit. The determinants of satisfaction include physical evidence, emotional factors, service quality, and tourist destination components (4A). This research aimed to (1) analyze the impact of physical evidence, emotional factors, service quality, and tourist destination components (4A) on consumer satisfaction and intention to revisit ecotourism and (2) formulate managerial implication obtained for the company to increase tourist visit. The population in this research was Terminal Wisata Grafika Cikole (TWGC) visitors. The sampling method used was convenience sampling with respondent criteria of at least 17 years old and visited TWGC at least once. There were 210 respondents in this research. The data were collected by asking the questionnaire questions through direct interviews with the TWGC visitor, then conducted in-depth interviews with 50 respondents to follow up with the research finding. Based on the research, physical evidence, emotional factors, and service quality positively impacted consumer satisfaction. Meanwhile, tourist destination components (4A) had no significant effect on customer satisfaction. Furthermore, consumer satisfaction had a positive impact on the intention to revisit. In conclusion, the higher consumer satisfaction, the higher the revisit interest. Keywords: components of tourist destinations, customer satisfaction, emotional factors, intention to revisit, physical evidence